Proximate Analysis of Palm Oil Waste Biobriquettes in East Kalimantan as an Alternative Energy Source in the Area Around the Nusantara Capital City-Indonesia - Vegatama, Meita Rezki (Pendidikan Kimia FKIP Universitas Jambi, 2024)
Renewable energy is an alternative energy that the government is strongly promoting to support energy security in the future, one of which is biomass energy. Oil palm plantations are quite extensive plantations in Indonesia; in fact, in one plantation, 9,155,722 tons of palm oil shell waste can be obtained/per year. Large quantities of palm oil shells can be processed into bio briquettes, so they have high economic value. This research aims to determine the approximate analysis of Palm Oil Waste Biobriquettes in East Kalimantan as an Alternative Energy Source Around the IKN Area. This research was carried out using experimental methods by making bio briquettes with analysis results obtained through laboratory analysis, namely proximate analysis. From the proximate analysis carried out on two repetitions of tests carried out on palm shell bio briquettes, only the water content still does not meet the SNI 01-6235-2000 standard. Namely, it is still above 8%. Still, of the other three parameters tested, all three have met the SNI standards of each, namely ash content below 8%, volatile matter content below 15%, and the calorific value of each is in the Ministry of Energy and Mineral Resources category, namely in category 3 with a calorific value range of 4700-5600 cal/g and SNI 01-6235-2000 with minimum 5000 cal/g.